Mapping the interactions between a RUN domain from DENND5/Rab6IP1 and sorting nexin 1. - KHAN, AMIR; FRANKLIN, EDWARD (My University, 2012)
Eukaryotic cells have developed a diverse repertoire of Rab GTPases to regulate vesicle trafficking pathways. Together with their effector proteins, Rabs mediate various aspects of vesicle formation, tethering, docking and fusion, but details of the biological roles elicited by effectors are largely unknown. Human Rab6 is involved in the trafficking of vesicles at the level of Golgi via interactions with numerous effector proteins. We have previously determined the crystal structure of Rab6 in complex with DENND5, alternatively called Rab6IP1, which comprises two RUN domains (RUN1 and RUN2) separated by a PLAT domain. The structure of Rab6/RUN1-PLAT (Rab6/R1P) revealed the molecular basis for Golgi recruitment of DENND5 via the RUN1 domain, but the functional role of the RUN2 domain has not been well characterized. Here we show that a soluble DENND5 construct encompassing the RUN2 domain binds to the N-terminal region of sorting nexin 1 by surface plasmon resonance analyses.
PUBLISHED
PubMed ID: 22558185
Keywords: soluble DENND5; soluble DENND5; Cancer